ANALISIS PERWUJUDAN GOOD GOVERNANCE MELALUI AKUNTABILITAS PUBLIK DAN MEMINIMALKAN PERILAKU OPORTUNISTIK DI DALAM LINGKUNGAN PEMERINTAHAN DAERAH - Yuanita, Dielanova Wynni (Universitas Islam Negeri Raden Intan Lampung, 2021)
Regional autonomy has decentralized subnational accounting system. Consequently, subnational government are supposed to enhance their accountability through a more transparent financial report. In other words, the implementation of good governance is compulsory in governmental vicinity. Budget is a tool of accountability, management, and economic decision; therefore, opportunistic behavior of legislatives and executives in arranging the budget might hamper the aspired good governance. The effort to minimize the opportunistic behavior is compulsory in governmental vicinity in order to enhance good governance system.